Length at first maturity of two species of lantern sharks (Etmopterus spinax and Etmopterus pusillus) off southern Portugal - Coelho, Rui (2016)
Etmoplerus spinax and Etmopterus pusillus are captured in large quantities in some deep-water fisheries along the Portuguesc coast and are always discarded. Specimens were collected from February 2003 to May 2004 from deep-water fisheries and classified as mature or immature. Maturity ogives were fitted and size at first maturity estimated for each sex of each of each species. Both species are late maturing, with the maturity size varying between 75% and 87% of the maximum observed sizes, depending on species and sex. For both species, females tended to mature at and grow to larger sizes than males. The late maturation of these deep-water shark species make these populations extremely vulnerable to increasing fishing mortality.